2018
DOI: 10.3390/w10030261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Timing and Interdependence of Hydrologic Processes at the Watershed Scale Based on Continuously Monitored Data

Abstract: A quantitative understanding of the interplay between the different components of the hydrologic cycle at the watershed scale can be gained from analyzing high-frequency hydrologic time series. High-frequency measurements of precipitation, soil water content, shallow groundwater, and streamflow were collected and analyzed in Otter Creek, a 122 km 2 watershed located in Northeast Iowa, USA. For selected rainfall events occurring in 2014, it was found that there is at least 4 h of delay between soil water conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…They reported quicker streamflow response to rainfall in the case of watersheds coupled with forests and steep topography compared to pasture and flat topography [8]. In another study, soil moisture was identified as a critical component in the development of the flood warning system [9].…”
Section: Introductionmentioning
confidence: 97%
“…They reported quicker streamflow response to rainfall in the case of watersheds coupled with forests and steep topography compared to pasture and flat topography [8]. In another study, soil moisture was identified as a critical component in the development of the flood warning system [9].…”
Section: Introductionmentioning
confidence: 97%
“…A multiple regression model was established to examine the average water level during two different periods (1960-1967 and 1968-1989) and precipitation in the current year, urban exploitation, peripheral exploitation and precipitation in the previous year. The following equations were used: Y = 30.417 + 0.002X 1 − 0.278X 2 + 0.002X 3 + 0.0004X 4 (13) Y = 27.362 + 0.002X 1 − 0.002X 2 − 0.05X 3 + 0.001X 4 (14) where X 1 is current precipitation; X 2 is urban exploitation; X 3 is external extraction; and X 4 is precipitation of the previous year. Regression analysis results (Table 2) show that from the 1960s to the 1990s, the main factor affecting groundwater level changed from precipitation to artificial exploitation, and the influence of peripheral mining has exceeded that of urban mining.…”
Section: Atmospheric Rainfall and Detection Of Spring Water Level Chamentioning
confidence: 99%
“…However, the loose rock type water and karst fissure water dynamics are quite different. A karst aqueous medium is highly heterogeneous and anisotropic, and its water circulation process is complex, resulting in karst fissures having a strong water flow [13,14]. This has led to an increase in laboratory-based physical model experiments investigating karst water flow movement [15,16].…”
Section: Introductionmentioning
confidence: 99%